2020
DOI: 10.1007/s10864-020-09399-x
|View full text |Cite
|
Sign up to set email alerts
|

Relational Operant Skills Training Increases Standardized Matrices Scores in Adolescents: A Stratified Active-Controlled Trial

Abstract: In recent years, small-scale studies have suggested that we may be able to substantially strengthen children's general cognitive abilities and intelligence quotient (IQ) scores using a relational operant skills training program (SMART). Only one of these studies to date has included an active Control Condition, and that study reported the smallest mean IQ rise. The present study is a larger stratified activecontrolled trial to independently test the utility of SMART training for raising Nonverbal IQ (NVIQ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In three studies, SMART was compared to an active control. Two studies compared SMART to a coding training program called Scratch (Hayes & Stewart, 2016; McLoughlin et al., 2020b), and one involved a control condition in which participants played chess (McLoughlin et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In three studies, SMART was compared to an active control. Two studies compared SMART to a coding training program called Scratch (Hayes & Stewart, 2016; McLoughlin et al., 2020b), and one involved a control condition in which participants played chess (McLoughlin et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the results of the present study, the wide confidence and prediction intervals should perhaps be interpreted with these factors in mind. In the two largest SMART studies to date (McLoughlin et al, 2020b(McLoughlin et al, , 2021, the authors found that attrition rates were related to baseline levels of trait negative emotion and trait agreeableness. It is possible that future large-scale SMART studies might benefit from providing additional supports for participants found to be relatively low in agreeableness or high in negative emotion to ensure that they stay motivated to take part.…”
Section: Limitations In the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Study 2, 30 typically developing participants demonstrated statistically significant improvements in educational aptitude, as measured by a standardized assessment, following relational training. Replication studies have also improved participant performance on full-scale IQ (FSIQ) compared to a waitlist control (Colbert et al, 2018) and on nonverbal IQ subscales compared to active controls (McLoughlin et al, 2020a, 2020b). Taken together, these findings suggest that derived relational responding is related to intelligence, that relational training improves scores on a wide range of standardized measures of intelligence, and that these changes may generalize to educational performance.…”
mentioning
confidence: 99%